Jens Sigsgaard og Ib Varnild (red.): »Det legede vi med ...« Gammelt legetøj i Danmark. (Nyt Nordisk Forlag Arnold Busck, 1982). 336 s. ill., 358,- kr. - Kjær, Birgitte (Historie/Jyske Samlinger, 1985)
-